Fighting the inevitable: infrastructure investment and coastal community adaptation to sea level rise. (31st August 2018) - Woodruff, Sierra; BenDor, Todd K.; Strong, Aaron L.
Abstract: Coastal communities are crafting adaptation strategies to confront sea level rise (SLR). Unfortunately, cost–benefit analyses that assess SLR risks often fail to capture important political and social feedbacks. For example, adaptation measures (e.g., beach nourishment) can trigger greater development, undermining the value of adaptation infrastructure, incentivizing development, and increasing risks. We integrate diverse literature and data to develop a hypothesis and system dynamics model of coastal community responses to SLR. We apply the model to two U.S. communities, showing how political influence drives trajectories of infrastructure provision, cost, and vulnerability. We find that delayed feedbacks between perceived SLR risk and infrastructure investments mediate relationships between political capital, migration, and economic development. Community wealth and political influence may only delay the overshoot and collapse of its population and economy, as the "virtuous cycles" linking growth with infrastructure investment give way to "vicious cycles" of mounting infrastructure costs, political resistance to additional investment, and greater vulnerability. Copyright © 2018 System Dynamics Society